Stress Kerja pada Perawat di Rumah Sakit - Fairuz Khanza Amalia; Fitria Saftarina; Putri Damayanti; Rika Lisiswanti (Pusat Riset dan Inovasi Nasional, 2026)
Work-related stress among nurses is a critical issue in modern healthcare, directly affecting patient safety, quality of care, and the well-being of nursing personnel. Work-related stress emerges from organizational factors such as high workload, unbalanced nurse-to-patient ratios, understaffing, and increased administrative demands. Operational stressors including night shifts, rapid rotations, and long working hours further intensify stress through disruptions in sleep patterns and circadian rhythms. Psychosocial pressures, such as constant exposure to critically ill patients, clinical trauma, death, and workplace violence add substantial emotional burden. Global studies consistently report high prevalence of moderate to severe stress among nurses. The impacts include emotional exhaustion, anxiety, depression, burnout, sleep disturbances, reduced immunity, and heightened clinical errors. Effective stress management requires comprehensive interventions at organizational, individual, and policy levels. Structural improvements, personal resilience training, and strong regulatory frameworks for healthcare worker protection are essential to build a safe, healthy, and sustainable work environment. Through an integrated approach, nurse stress management can enhance healthcare quality while ensuring the resilience of the broader health system.